Biofilm-derived Legionella pneumophila evades the innate immune response in macrophages - Abu Khweek, Arwa; Fernández Dávila, Natalia; Caution, Kyle; Akhter, Anwari; Abdulrahman, Basant; Tazi, Mia; Hassan, Hoda; Novotny, Laura; Bakaletz, Lauren; Amer, Amal O. (Frontiers in Cellular and Infection Microbiology, 2013)
Legionella pneumophila, the causative agent of Legionnaire's disease, replicates in human alveolar macrophages to establish infection. There is no human-to-human transmission and the main source of infection is L. pneumophila biofilms established in air conditioners, water fountains, and hospital equipments. The biofilm structure provides protection to the organism from disinfectants and antibacterial agents. L. pneumophila infection in humans is characterized by a subtle initial immune response, giving time for the organism to establish infection before the patient succumbs to pneumonia. Planktonic L. pneumophila elicits a strong immune response in murine, but not in human macrophages enabling control of the infection. Interactions between planktonic L. pneumophila and murine or human macrophages have been studied for years, yet the interface between biofilm-derived L. pneumophila and macrophages has not been explored. Here, we demonstrate that biofilm-derived L. pneumophila replicates significantly more in murine macrophages than planktonic bacteria. In contrast to planktonic L. pneumophila, biofilm-derived L. pneumophila lacks flagellin expression, do not activate caspase-1 or -7 and trigger less cell death. In addition, while planktonic L. pneumophila is promptly delivered to lysosomes for degradation, most biofilm-derived bacteria were enclosed in a vacuole that did not fuse with lysosomes in murine macrophages. This study advances our understanding of the innate immune response to biofilm-derived L. pneumophila and closely reproduces the natural mode of infection in human.